La2O3-encapsulated SnO2 nanocrystallite-based photoanodes for enhanced DSSCs performance - Shaikh, Shoyebmohamad F.; Mane, Rajaram S.; Joo, Oh-Shim (ROYAL SOC CHEMISTRY, 2015)
A SnO2 nanocrystallite-based photoanode was prepared using tin (IV) chloride and fructose via a one-pot hydrothermal method, and its structural and morphological properties were studied. Structural observations revealed tetragonal crystals of SnO2, and morphological studies confirmed the presence of spherical nanoparticulates. Furthermore, encapsulating the surface of the SnO2 photoanode (+N719 dye) with thin layers of La2O3 significantly improved the short-circuit current density, open-circuit voltage, fill factor and power conversion efficiency values from 8.30 to 13.70 mA cm(-2), 0.40 to 0.46 V, 49% to 48% and 1.66% to 3.0%, respectively. The nearly two-fold improvement in energy conversion efficiency was attributed to: (a) increased dye molecules caused by the formation of strong co-ordination bonds between the dye molecules and the lanthanide, (b) enhanced photoelectron transfer rate between the dye molecules and SnO2 conduction band, and (c) negative shift of SnO2 conduction band position in the presence of La2O3 (confirmed from the Mott-Schottky and Tafel measurements).
Keywords: SENSITIZED SOLAR-CELLS; SURFACE MODIFICATION; ELECTRON-TRANSPORT; TIN OXIDE; TIO2; CONVERSION; INTERFACE; LAYER; SHELL; FILM